2017
DOI: 10.1016/j.rmed.2016.12.012
|View full text |Cite
|
Sign up to set email alerts
|

How many instructions are required to correct inhalation errors in patients with asthma and chronic obstructive pulmonary disease?

Abstract: In the treatment of asthma and chronic obstructive pulmonary disease (COPD), errors in handling and wrong techniques in using inhalation devices are associated with poor disease control. The aim of this study was to evaluate the number of instructions that are necessary to minimize errors in using pressurized metered-dose inhaler (pMDI), soft mist inhaler (SMI), and dry powder inhaler (DPI). Among 216 patients with asthma (n = 135) and COPD (n = 81), we studied 245 cases that used different types of inhalation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
98
0
6

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(112 citation statements)
references
References 20 publications
(10 reference statements)
8
98
0
6
Order By: Relevance
“…Our study confirmed that both new and continuous users of inhalers require attention. In addition, one study suggests that it takes at least three educational sessions by a trained pharmacist to correct inhalation errors [35]. A systematic review of the effectiveness of inhaler technique interventions concluded that the effect decreases over time, which signals the need for periodic reinforcement strategies [36].…”
Section: Discussionmentioning
confidence: 99%
“…Our study confirmed that both new and continuous users of inhalers require attention. In addition, one study suggests that it takes at least three educational sessions by a trained pharmacist to correct inhalation errors [35]. A systematic review of the effectiveness of inhaler technique interventions concluded that the effect decreases over time, which signals the need for periodic reinforcement strategies [36].…”
Section: Discussionmentioning
confidence: 99%
“…Among these articles, 33 did not provide information on device use errors, resulting in a total of 12 publications that were included in this meta-analysis. 22,[39][40][41][42][43][44][45][46][47][48][49] Since this study involved reviewing aggregate level secondary data published in publicly available studies and there was no access to primary patient-level data, protocol approval by the Institutional Review Board and Ethical Committee was waived.…”
Section: Search Strategymentioning
confidence: 99%
“…Significant heterogeneity was observed across the 12 studies included in our meta-analysis (I 2 ¼ 92.8%; test for heterogeneity: Q(df ¼ 11): 273.6, p < 0.001). Sensitivity analysis revealed that the pooled effect size was altered with the removal of five studies 22,39,41,44,49 (Figure 4). The resulting overall effect size was 57.5% (95% CI: 21.2-93.9) across the five studies relative to 59.8% (95% CI: 51.3-68.4) for the remaining seven studies.…”
Section: Heterogeneity and Sensitivity Analysismentioning
confidence: 99%
“…It has been shown that most inhaler users not only make errors but also those patients who did not get proper education on inhaler technique are more inclined to misuse their device [82]. A recent Japanese study has also suggested that patients, regardless of having asthma or COPD, require to be instructed at least three times, i.e., given demonstrations by trained personnel in order to limit inhaler handling errors [83]. Notably, while about 65% of patients made at least one handling error that could affect the efficacy after an initial guidance on how to use the Breezhaler Ò , the Ellipta Ò or Respimat Ò , more than 90% of patients using any device could successfully learn the correct use after receiving guidance from pharmacists three times successively [83].…”
Section: Handling Of Inhaler Devicesmentioning
confidence: 99%
“…A recent Japanese study has also suggested that patients, regardless of having asthma or COPD, require to be instructed at least three times, i.e., given demonstrations by trained personnel in order to limit inhaler handling errors [83]. Notably, while about 65% of patients made at least one handling error that could affect the efficacy after an initial guidance on how to use the Breezhaler Ò , the Ellipta Ò or Respimat Ò , more than 90% of patients using any device could successfully learn the correct use after receiving guidance from pharmacists three times successively [83]. Whether inhaler handling errors remain frequent among longterm inhaler users or are associated with worse clinical outcomes in COPD is discussed below.…”
Section: Handling Of Inhaler Devicesmentioning
confidence: 99%